ANALISA KEKASARAN PERMUKAAN PROSES BOR BAJA SKD 11 PADA MESIN CNC - Pajar Juliansah; Zulfitriyanto Zulfitriyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The best quality of a component is a smooth surface. To achieve an optimum response, the variable setting of the process must be correct to be effective. SKD 11 steel includes the kind of tool steel that is frequently applied in the manufacturing industry as cutting tools, shear blades, stamping tools, punching, dies, and so on. Therefore, it is expected to have good surface roughness. This research will use a combination of variables to process spindle, feed rate, and cooling. The method used was experimental methods with tuning parameters. Based on research shows the most optimum gross response value was the 1600 RPM index, the rate of 120 mm per minute, and the cooling type of dramas. Variables that contribute significantly to the total variance of rudeness are the feed rate of 67.43 %.